Paleolithic subsistence strategies and changes in site use at Klissoura Cave 1 (Peloponnese, Greece). Issue 111 (October 2017) - Starkovich, Britt M.
Abstract: Klissoura Cave 1 in southern Greece preserves a long archaeological sequence that spans roughly 90, 000 years and includes Middle Paleolithic, Uluzzian, Upper Paleolithic, and Mesolithic deposits. The site provides a unique opportunity to examine diachronic change and shifts in the intensity of site use across the Late Pleistocene. There is an overall picture of the intensified use of faunal resources at the site, evidenced by a shift from large to small game, and to small fast-moving taxa in particular. This trend is independent of climatic change and fluctuations in site use, and most likely reflects a broader, regional growth of hominin populations. At the same time, multiple lines of evidence (e.g., input of artifacts and features, sedimentation mechanisms, and intensification of faunal resources) indicate that the intensity of site use changed, with a sharp increase from the Middle Paleolithic to Aurignacian. This allows us to address a fundamental issue in the study of human evolution: differences in population size and site use between Neandertals and modern humans. At Klissoura Cave 1, the increase in occupation intensity might be related to population growth or larger group size, but it might also be due to changes in season of site use, more favorable environmental conditions at the beginning of the Upper Paleolithic, and/or changes in the composition of people occupying the site. These explanations are not necessarily mutually exclusive, and indeed the data support a combination of factors. Ascribing the increase in occupation intensity to larger Upper Paleolithic populations more broadly is difficult, particularly because there is little consensus on this topic elsewhere in Eurasia. The data are complicated and vary greatly between sites and regions. This makes Klissoura Cave 1, as the only currently available case study in southeastern Europe, a critical example in understanding the range of variation in demography and site use across the Middle to Upper Paleolithic transition.